Artificial Intelligence/Machine Learning in Pharma Analysis and Quality Control: A Real-World Upgrade - Jain, Kishor; Kadam, Deepali; Thakur, Sarathi; Dhole, Pranali (Indian Journal of Pharmaceutical Education and Research)
Pharmaceutical analysis and quality control are now being transformed by Artificial Intelligence (AI) and Machine Learning (ML) through remarkable improvement in speed, accuracy, reliability, robustness of analysis methods. This review is to explore the integration of these tools into raw material inspection, in-process monitoring, and finished product analysis. A comprehensive survey of published literature, regulatory documents, and case studies was conducted. Key AI/ ML paradigms Supervised, Unsupervised, Deep learning, Reinforcement learning, NLP; as the most important AI/ML paradigms were analysed, besides chemometrics and data management strategies in context to pharmaceuticals. Applications of AI/ML have demonstrated significant improvements in predictive quality assurance, defect detection, impurity profiling, and stability prediction. Further, their integration with Process Analytical Technology (PAT) and digital twins have enabled real-time monitoring and proactive quality management. The adoption of AI/ML is a paradigm shift from reactive to proactive Quality Control. Though data quality, regulatory compliance, and ethical considerations pose challenges, the future trends namely, integration of the explainable AI, federated learning, and robotics do promise robust, transparent, and efficient pharmaceutical quality systems.
Keywords: Artificial intelligence (AI); Machine learning (ML); Pharmaceutical Analysis and Quality Control; Process Analytical Technology (PAT)